The Power to Tax; the Need to Provide - King, Dennis (Maine Policy Review, 1997)
Pointing to the vital role nonprofit organizations fill in providing services for those in need, Dennis King in the Margaret Chase Smith Essay suggests carefully considering the trend toward taxation of this sector, and weigh it against alternative, revenue-generating strategies that reinforce rather than strain the relationship between government and nonprofit charities.
Keywords: Maine tax policy; Maine tax code; nonprofit organizations